Demand Forecasting as an Element of the Company's Financial Security during the Warehouse Processes - Malgorzata GRZELAK; Paulina OWCZAREK; Weronika DORF (Communications of International Proceedings, 2021)
Financial security determines the company's ability to raise funds when needed. In times of the COVID-19 pandemic, which causes a number of disruptions in the supply chain, the ability to accurately predict the size of the financial flow that will flow to the company is extremely important. One of the possibilities to support financial decision-making is to develop tools that enable forecasting of demand, and then, on this basis, create financial plans. The aim of the article was to develop a multivariate regression model that will enable a simple prediction of income based on the estimated size of the transported cargo. The study was conducted on the basis of data on the sale of organic food based on the e-commerce channel. The factors having a significant impact on the studied phenomenon were selected, the parameters of the models were estimated, and the analysis and evaluation were carried out based on the verification of the normality of the distribution of residuals and the function of their autocorrelation. The obtained results allowed for a detailed analysis of the expected financial result and testified to the financial security of the entity.
Keywords: Financial Security; Multiple Regression; Demand Forecasting.